Rancang Bangun Alat Pengering Tenaga Surya (Solar Dryer) Portabel Berbentuk Prisma Segitiga - Iklas Sanubary; Iman Syahrizal; Mizan Junaidi (Politeknik Negeri Padang, 2023)
This research aims to design a solar dryer to increase drying room temperature. The drying room is designed in the shape of a triangular prism. The dried test material is Arabica coffee. The method used in this research is experimental by comparing the drying results in a solar dryer (inside) and traditional method (outside). Data collection was carried out for 3 days, starting at 09.00 WIB to 15.00 WIB with intervals every 1 hour. The data measured are the temperature inside and outside the solar dryer and the mass of the test material before and after drying. The results showed that the difference in the average temperature measured inside and outside the solar dryer on day 1 was 11.1 oC, on day 2 it was 11.6 oC and on day 3 it was 8.3 oC. The total mass reduction of the test material during 3 days of drying inside the solar dryer was 180.91 gram and outside the solar dryer was 164.03 gram. The average drying rate inside the solar dryer was 10 gram/hour while outside the solar dryer was 9.1 gram/hour. Based on these result, solar dryer can produce higher temperatures, greater mass reduction and higher drying rates than traditional methods